Pengaruh Metode Pembelajaran Game Based Learning Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di SMP Muhammadiyah 57 - Savana, Bunga; Nst, Najwa Amalina; Zahra, Sa'diyyah (Journal of Sustainable Education, 2025)
The selection of learning methods in the learning process is one of the steps that a teacher must take when teaching. In the learning process, teachers are required to use learning methods which are interesting and also always involve students in learning. If a teacher chooses the right learning method and also students are interested in the learning, then it can be said that the learning process is successful. Research conducted by researchers at SMP Muhammadiyah 57 shows that the learning process still uses the Teacher Center learning system, a system that is still teacher-centred and not student-centred. So that many students are less actively involved and also creative in the learning process. In this study, the Game Based Learning method was used. This study aims to determine the effect of Game Based Learning learning method on student learning outcomes in Islamic Religious Education subjects at SMP Muhammadiyah 57.